Long Island a novel - Tóibín, Colm 1955- (Scribner, 2024)
"Eilis Lacey is Irish, married to Tony Fiorello, one of four Italian American brothers, all of whom live in neighboring houses on a cul-de-sac in Lindenhurst, Long Island, with their wives and children and Tony's parents, a huge extended family that lives and works, eats and plays together. It is the spring of 1976 and Eilis, now in her forties with two teenage children, has no one to rely on in this still-new country. Though her ties to the town in Ireland where she grew up remain stronger than those that hold her to her new land and home, she has not returned in decades. One day, when Tony is at his job, an Irishman comes to the door asking for her by name. He tells her that his wife is pregnant with Tony's child, and that when the baby is born, he will not raise it but instead will deposit it on Eilis's doorstep. It is what Eilis does - and what she refuses to do - in response to this stunning news that makes Tóibín's novel so riveting. Long Island is about longings unfulfilled, even unrecognized. The silences in Eilis's life are thunderous and dangerous, and there's no one defter than Tóibín at giving them language. This is a gorgeous story of a woman alone in a marriage and the deepest of bonds she rekindles on her return to the place and people she left behind, to ways of living and loving she thought she'd lost. Eilis is perhaps Tóibín's most moving and unforgettable character, and this novel is a masterpiece"--
Keywords: Novels; Romans; Fiktionale Darstellung